2008
DOI: 10.1042/bj20080782
|View full text |Cite
|
Sign up to set email alerts
|

SMILE, a new orphan nuclear receptor SHP-interacting protein, regulates SHP-repressed estrogen receptor transactivation

Abstract: SHP (small heterodimer partner) is a well-known NR (nuclear receptor) co-regulator. In the present study, we have identified a new SHP-interacting protein, termed SMILE (SHP-interacting leucine zipper protein), which was previously designated as ZF (Zhangfei) via a yeast two-hybrid system. We have determined that the SMILE gene generates two isoforms [SMILE-L (long isoform of SMILE) and SMILE-S (short isoform of SMILE)]. Mutational analysis has demonstrated that the SMILE isoforms arise from the alternative us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 52 publications
2
76
0
1
Order By: Relevance
“…Our qRT-PCR experiment, however, revealed that NR0B1 mRNA expression is undetectable in mouse liver tissues (data not shown). Also, SHP-interacting leucine zipper protein (SMILE) [initially identified as an SHP-interacting protein (Xie et al, 2008)] has been shown to repress HNF4a transactivation of target genes in the absence of SHP . Our results showed, however, that the mRNA expression levels of SMILE did not differ between Shp(2/2);CYP2D6 and Shp (+/+);CYP2D6 male mice (data not shown; in female mice, SMILE mRNA expression was even lower in Shp(2/2);CYP2D6 mice as compared with Shp(+/+);CYP2D6 mice).…”
Section: Discussionmentioning
confidence: 99%
“…Our qRT-PCR experiment, however, revealed that NR0B1 mRNA expression is undetectable in mouse liver tissues (data not shown). Also, SHP-interacting leucine zipper protein (SMILE) [initially identified as an SHP-interacting protein (Xie et al, 2008)] has been shown to repress HNF4a transactivation of target genes in the absence of SHP . Our results showed, however, that the mRNA expression levels of SMILE did not differ between Shp(2/2);CYP2D6 and Shp (+/+);CYP2D6 male mice (data not shown; in female mice, SMILE mRNA expression was even lower in Shp(2/2);CYP2D6 mice as compared with Shp(+/+);CYP2D6 mice).…”
Section: Discussionmentioning
confidence: 99%
“…The reporter plasmids LXRE-Luc, SREBP1c-Luc, and SMILE-Luc were described previously (12,17). pCMV-␤-gal, pcDNA3-HA-LXR␣, pcDNA3-HA-SRC-1, pcDNA3-ERR␥, pcDNA3-FLAG-SMILE, pGEX4T-1, pGEX4T-1-SMILE, pEBGempty, pEBG-SMILE, pSUPER-si-empty, and pSUPER-si-SMILE, FLAG-SMILE LXXLL mutants (m1, m2, m3, m4, and m5) were described previously (12,15,17). pEBG-LXR␣ WT, pEBG-LXR␣ C, pEBG-LXR␣ DE, and pEBG-LXR␣ AB were subcloned into the BamHI/KpnI sites of the pEBG vector.…”
Section: Methodsmentioning
confidence: 99%
“…SMILE has also been proposed as a coactivator of activating transcription factor 4 (14). Moreover, we have revealed that SMILE functions as a nuclear co-repressor of the estrogen receptor (ER), glucocorticoid receptor (GR), constitutive androstane receptor (CAR), hepatocyte nuclear factor 4␣, and estrogen receptor-related receptor ␥ (ERR ␥) (15)(16)(17). Moreover, we reported that curcumin induces SMILE gene expression through a liver kinase B1/adenosine monophosphate-activated kinase (AMPK) pathway and represses endoplasmic reticulum (ER) stress-responsive gene transcription (18).…”
Section: Small Heterodimer Partner Interacting Leucine Zipper Proteinmentioning
confidence: 99%
“…Small heterodimer partner-interacting leucine zipper protein (SMILE), including two alternative translation-derived isoforms, SMILE-L (CREBZF: long form of SMILE) and SMILE-S (Zhangfei: short form of SMILE), has been classified as a member of the CREB/ATF family of basic regionleucine zipper transcription factors. However, SMILE cannot bind to DNA as a homodimer (10)(11)(12). SMILE has also been reported to function as a coactivator of activating transcription factor 4 or as a corepressor of host cell factor-binding transcription factor (13,14).…”
mentioning
confidence: 99%